2020
DOI: 10.3389/fvets.2020.00638
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Benchmarking High Antimicrobial Usage Farms Based on Either Animal Treatment Index or Number of National Defined Daily Doses

Abstract: Introduction: While treatment frequency as an indicator of antimicrobial consumption is often assessed using defined doses, it can also be calculated directly as an Animal Treatment Index (ATI). In this study, the correlation of calculating antimicrobial usage on Swiss pig farms using either national Defined Daily Doses (DDDch) or an ATI (number of treatments per animal per year) and the agreement between the different methods for the identification of high usage farms were investigated. Material and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This enzyme can elevate the levels of mitogenic metabolites in cancer cells and thus increase the proliferation rate of cancers (37,38). Recently, Bo Chu et al found that ALOX12 inactivation diminishes p53-mediated ferroptosis induced by ROS stress and abrogates p53dependent inhibition of tumour growth (17), which means that ALOX12 might function as a hub gene with a deep connection with many essential FRLs. We also noticed that LINC02831 had high correlations with 3 mRNAs (NOX4, ALOX15B, and CDO1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme can elevate the levels of mitogenic metabolites in cancer cells and thus increase the proliferation rate of cancers (37,38). Recently, Bo Chu et al found that ALOX12 inactivation diminishes p53-mediated ferroptosis induced by ROS stress and abrogates p53dependent inhibition of tumour growth (17), which means that ALOX12 might function as a hub gene with a deep connection with many essential FRLs. We also noticed that LINC02831 had high correlations with 3 mRNAs (NOX4, ALOX15B, and CDO1).…”
Section: Discussionmentioning
confidence: 99%
“…zhounan.org/ferrdb/index.html) and contained 121 validated human FRGs. Subsequently, Spearman correlation coefficients were calculated based on FRGs and lncRNA expression profiles to identify FRLs (|R 2 |>0.4 and p < 0.001) (17).…”
Section: Identification Of Ferroptosis-related Lncrnasmentioning
confidence: 99%
“…Generally in any benchmarking system, the choice of AMU metric will affect the identification of high usage farms. Example, for Swiss pig farms Kuemmerlen et al ( 19 ) investigated how well two metrics, the number of DDDch's and the number of treatments, both taken per animal and year, agreed when benchmarking levels of antimicrobial usage and identifying high users. They found that although the two metrics were strongly correlated and showed broad agreement certain proportions of farms were categorized differently, and that these proportions varied by age category and benchmarking threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis. To explore the correlation genes with HDAC7, the Sanger box-Spearman correlation coefficients calculator was used to calculated the correlation confidence of HDAC7-related genes, the criteria of correlation genes were |R|>=0.4 and a P<0.05 (39). Then the result was plotted as heat map using the OmicStudio tools V3.3.6 (omicstudio.cn/tool).…”
Section: Methodsmentioning
confidence: 99%